2003
DOI: 10.1074/jbc.m209344200
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Three Drosophila melanogaster Glucuronyltransferases Responsible for the Synthesis of the Conserved Glycosaminoglycan-Protein Linkage Region of Proteoglycans

Abstract: The Drosophila melanogaster genome contains three putative glucuronyltransferases homologous to human GlcAT-I and GlcAT-P. These enzymes are predicted to be ␤1,3-glucuronyltransferases involved in the synthesis of the glycosaminoglycan (GAG)-protein linkage region of proteoglycans and the HNK-1 carbohydrate epitope of glycoproteins, respectively. The genes encode active enzymes, which we have designated DmGlcAT-I, DmGlcAT-BSI, and DmGlcAT-BSII (where BS stands for "broad specificity"). Protein A-tagged truncat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 53 publications
(34 reference statements)
1
36
0
Order By: Relevance
“…3 Instead, it is tempting to speculate that GlcA serves as the sialic acid equivalent in Drosophila. The occurrence of terminal GlcA on Drosophila glycosphingolipids and of terminal sialic acid on the vertebrate ganglioside family of glycosphingolipids is also consistent with functional equivalence between these two acidic monosaccharides (74,75,77). However, distinct differences indicate that this hypothesis is probably an oversimplification.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…3 Instead, it is tempting to speculate that GlcA serves as the sialic acid equivalent in Drosophila. The occurrence of terminal GlcA on Drosophila glycosphingolipids and of terminal sialic acid on the vertebrate ganglioside family of glycosphingolipids is also consistent with functional equivalence between these two acidic monosaccharides (74,75,77). However, distinct differences indicate that this hypothesis is probably an oversimplification.…”
Section: Discussionmentioning
confidence: 77%
“…Some of these activities have been described in other species or are evident in the biosynthesis of Drosophila glycosphingolipids and glycosaminoglycans (77,95). However, in the context of O-linked core 1 or core 2 or O-Fuc, these modifications are novel, and identification of the relevant biosynthetic enzymes will provide new opportunities for dissecting the functions of O-linked glycans.…”
Section: Discussionmentioning
confidence: 99%
“…Two genes, GlcAT-P and PAPS appear to be particularly strong candidates. Expression of GlcAT-P, encoding a putative N-acetyllactosamine ␤-1,3-glucuronosyltransferase (Kim et al, 2003) was reduced to one thirtieth of its original levels. This gene has been implicated in glycoprotein, glycosphingolipid and proteoglycan biosynthesis.…”
Section: Spermathecae Express Genes That May Modify and Capacitate Spermmentioning
confidence: 99%
“…Many enzymes involved in linkage structure formation, sulfation and/or phosphorylation, and chain polymerization of these structures have been carefully characterized, but we have yet to understand even the most rudimentary regulatory mechanism involved in this process [11,23,48,49]. Empirical evidence has shown that CS chain length, as well as the location and degree of modifications, can vary along the core protein of aggrecan [50,51].…”
Section: Discussionmentioning
confidence: 99%